Clients of Street Prostitutes in Portland, Oregon, San Francisco and Santa Clara, California, and Las Vegas, Nevada, 1996-1999 - Monto, Martin A. ([Verlag nicht ermittelbar], 2000)
These data were collected to examine the background characteristics, attitudes, and reported behaviors of arrested clients of prostitutes, with particular attention to the issue of violence against women. Client intervention programs in four cities provided opportunities for gathering information from men arrested for trying to hire street prostitutes. For the study, a detailed anonymous questionnaire was administered to men before the beginning of every client intervention workshop in San Francisco, California, and Portland, Oregon. The questionnaire was also administered at a small program in Santa Clara, California, which was modeled after the San Francisco program. During the course of the study, the Portland program ceased operations and a new program began in Las Vegas, which became a significant source of data. Men were asked about their sexual behavior, including the number and type of partners, frequency of sex, interest in pornography, age and circumstances of first sexual encounter with a prostitute, sexual acts performed with prostitutes, and condom use with prostitutes. Clients were also asked about their attitudes toward premarital sex, homosexual sex, extramarital sex, and sex between adults and children. Other questions probed men's views about prostitutes, the legality of prostitution, and violence against women. Background information gathered on clients included race, educational level, sexual orientation, marital status, work status, socioeconomic status, age, parents' marital status, history of sexual or physical abuse, military service, relationship history, and sexual preferences.